MENINGKATKAN PENDAPATAN KELUARGA MELALUI PELATIHAN KERAJINAN TANGAN DI GAMPONG RANTAU PANYANG TIMUR KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Leli Putri Ansari; Ivon Jalil; Yayuk Eko Wahyuningsih; Yasrizal Yasrizal; Said Mahdani (Jurnal Pengabdian Agro and Marine Industry, 2021)
One of the activities that increase family income can is through handicraft training. The handicraft training taught was the manufacture of synthetic pearl brooches which was held in Gampong Rantau Panyang Timur, Meureubo District, West Aceh Regency, where most of the people live in the agricultural sector and earn their living as farmers. This training is intended for housewives who are members of the PKK (Family Welfare Empowerment) forum and aims to train skills in making brooches made from synthetic pearls with unique, varied and high selling value models, as well as foster an entrepreneurial spirit so that after this training activity finished, they continue to start a business such as a synthetic pearl brooch souvenir business that is a home industry. Thus it can help to increase the husband's income so that family income also increases. Besides, it also has an impact on the economy of the surrounding community because it can absorb workers specifically for women. The method in this activity was the lecture and practice which was attended by 28 participants. The results of this activity received a very good response from the participants and they were very enthusiastic to participate the training on making synthetic pearl brooches, and they hoped that there would be other training that could hone skills that could potentially increase family income.